Identification of prognostic factors and assessment methods on the evaluation of non-specific low back pain in a biopsychosocial environment: A scoping review. (December 2018) - Draper-Rodi, Jerry; Vogel, Steven; Bishop, Annette
Highlights: This review lists biopsychosocial factors and assessment methods to use with non-specific low back pain. These should be included in evidence-informed educational interventions. This review supports a biopsychosocial approach in a manual therapy context.